EULAR recommendations for the role of the nurse in the management of chronic inflammatory arthritis. Issue 1 (28th October 2011) - van Eijk-Hustings, Yvonne; van Tubergen, Astrid; Boström, Carina; Braychenko, Elena; Buss, Beate; Felix, José; Firth, Jill; Hammond, Alison; Harston, Benny; Hernandez, Cristina; Huzjak, Masa; Korandová, Jana; et al.
Abstract : Objectives: The authors aim to develop European League Against Rheumatism recommendations for the role of the nurse in the management of patients with chronic inflammatory arthritis, to identify a research agenda and to determine an educational agenda. Methods: A task force made up of a multidisciplinary expert panel including nurses, rheumatologists, occupational therapist, physiotherapist, psychologist, epidemiologist and patient representatives, representing 14 European countries, carried out the development of the recommendations, following the European League Against Rheumatism standardised operating procedures. The task force met twice. In the first meeting, the aims of the task force were defined, and eight research questions were developed. This was followed by a comprehensive, systematic literature search. In the second meeting, the results from the literature review were presented to the task force that subsequently formulated the recommendations, research agenda and educational agenda. Results: In total, 10 recommendations were formulated. Seven recommendations covered the contribution of nurses to care and management: education, satisfaction with care, access to care, disease management, psychosocial support, self-management and efficiency of care. Three recommendations focused on professional support for nurses: availability of guidelines or protocols, access to education and encouragement to undertake extended roles. The strength of the recommendations varied from A to C, dependent on the category of evidence (1A–3), and a high level of agreement was achieved. Additionally, the task force agreed upon 10 topics for future research and an educational agenda. Conclusion: 10 recommendations for the role of the nurse in the management of chronic inflammatory arthritis were developed using a combination of evidence-based and expert consensus approach.